Biochar changes thermal activation of greenhouse gas emissions in a rice–lettuce rotation microcosm experiment. (20th February 2020) - Qi, Le; Pokharel, Prem; Ni, Chengsheng; Gong, Xiaoqiang; Zhou, Peng; Niu, Haidong; Wang, Zifang; Gao, Ming
Abstract: Despite numerous studies of the effects of biochar amendments on soil greenhouse gas (GHG) emissions in recent years, the intrinsic temperature sensitivity of GHG emissions in biochar-amended soils is still not clear. In order to investigate the effects of biochar on the thermal activation of GHG emissions, the GHG emissions and their activation energies ( E a ) were analyzed in a rice-lettuce rotation microcosm experiment. The experiment had five treatments: control (CK), chemical fertilizers (NPK), and three biochar application rates that are equivalent to 10 Mg ha −1 biochar (BC10 ), 20 Mg ha −1 biochar (BC20 ) and 40 Mg ha −1 biochar (BC40 ). The study showed that biochar treatments reduced CO2 and N2 O emissions by lowering their E a compared with the NPK treatment in the rice cultivation season. The biochar amendment treatments significantly reduced N2 O cumulative emissions by 55.2–72.9% compared with the NPK treatment in the lettuce cultivation season largely due to the thermally deactivated impact of soil temperature on N2 O emissions. Microbial biomass carbon was increased in the lower rates of biochar amendment in both crop cultivation seasons. These findings suggest that biochar amendment of soil has the potential to decrease the positive and increase the negative E a of GHG emissions, with the implication of mitigating GHG emissions from cropland soils that would otherwise be increased by applying chemical fertilizers in the context of rising global temperature. Production of biochar from agricultural wastes, which is a method of cleaner production, and its application to the soil shows its potential for reducing GHG emissions by changing the thermal activation of the emissions during rice–lettuce crop rotation. Graphical abstract: Notes: The smaller blue circle represented the thermal activation was higher which implied lower energy was needed to transfer greenhouse gas emissions to other substance. The larger orange circle implied more energy is needed for GHG production. The blue arrow represented the E a of the GHG emission was positive and the orange arrow represented the E a of the GHG emission was negative. The green arrow represented the GHG emission was decreased in all the biochar amended treatment as compared to NPK treatment. Image 1 Highlights: Biochar's effect on GHG emissions was evaluated using Arrhenius equation. Activation energies ( E a ) of GHG fluxes were calculated in a rice-vegetable crop rotation. The E a of CO2 fluxes were decreased by 34.6–42.3% by biochar amendments under anaerobic condition. Decrease in E a for N2 O fluxes decreases in N2 O emission via biochar addition. Soil CH4 and CO2 emissions were affected by soil temperature, SOC, DOC and MBC.